2018
DOI: 10.4315/0362-028x.jfp-18-150
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Addition of Functional Plant Extracts and Baking Conditions To Develop Acrylamide-Free Pita Bread

Abstract: The effects of using freeze-dried extracts (FDEs) of spearmint ( Mentha spicata), fennel ( Foeniculum vulgare), and turmeric ( Curcuma longa) as well as adjusting the baking temperature and time on acrylamide formation in pita bread were investigated to obtain the most acceptable conditions that produced the lowest acrylamide concentrations. A Box-Behnken design was adopted for optimization of the pita bread formulations by adding FDEs (3 to 25 g/100 g of wheat flour) and adjusting the baking temperature (200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Different studies have reported on the effects of antioxidants such as ascorbyl palmitate, sodium ascorbate, butylated hydroxytoluene (BHT), vitamin E, sesamol, antioxidants from extracts of various spices and herbs such as oregano, cranberry, rosemary, cumin, anise, green tea, turmeric, ginger, etc. on acrylamide reduction in foodstuffs [2,23,[150][151][152][153]. Nowadays there is an increasing trend towards the use of natural antioxidants obtained from spices and herb extracts in food products, including bakery ones, to reduce the formation of AA in these foods due to the fact that the consumers are demanding natural foods without preservatives.…”
Section: Use Of Antioxidants In Bakery Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have reported on the effects of antioxidants such as ascorbyl palmitate, sodium ascorbate, butylated hydroxytoluene (BHT), vitamin E, sesamol, antioxidants from extracts of various spices and herbs such as oregano, cranberry, rosemary, cumin, anise, green tea, turmeric, ginger, etc. on acrylamide reduction in foodstuffs [2,23,[150][151][152][153]. Nowadays there is an increasing trend towards the use of natural antioxidants obtained from spices and herb extracts in food products, including bakery ones, to reduce the formation of AA in these foods due to the fact that the consumers are demanding natural foods without preservatives.…”
Section: Use Of Antioxidants In Bakery Productsmentioning
confidence: 99%
“…The addition of spices such as rosemary to wheat flour helps reduce the formation of AA when it is added to the dough before the heat treatment is applied [2]. Antioxidants such as phenolic compounds, flavonoids, vitamins, and phenolic extracts from various spices (thyme, cumin and anise and so on), herb extracts (green tea, mint, fennel, turmeric) have been reported as inhibiting acrylamide formation [150][151][152]. One of the most used natural antioxidants in foodstuffs, including bakery ones, in order to reduce the AA content is rosemary (Rosmarinus officinalis L.), for which very good results have been reported.…”
Section: Use Of Antioxidants In Bakery Productsmentioning
confidence: 99%
“…Additionally, acrylamide may be formed via deamination of 3-aminopropionamide or directly by azomethine ylide ( 87 , 88 ). Constituents of the flour play major roles in acrylamide formation, and acrylamide is formed in higher concentrations in bread manufactured with high extraction rate flours ( 89 ). For this reason, improving the functional value of bread by incorporating the outer layer of cereal dietary fiber becomes very challenging and, to overcome related difficulties, new ingredients such as psyllium husks can be very promising.…”
Section: Resultsmentioning
confidence: 99%